Sexual Behaviour in Native Cattle and Buffalo Bulls and its Consequences for Welfare and Quality Semen Production (Indian Journal of Animal Production and Management, 2024)
Sexual behaviour in cattle and buffaloes is  influenced by various factors such as seasonality,  reproductive physiology, and social dynamics. This  behaviour includes reaction time, courtship, sexual  aggressiveness, penile erection, and ejaculatory  thrust. Testosterone, kisspeptin and pheromones  significantly influence sexual behaviour affecting  reaction time, sexual aggressiveness, and penile  erection. In addition, environmental conditions can  impact the physiological aspects of bulls, including  hormone secretion, energy metabolism and fatty  acid oxidation. These factors subsequently  influence the sexual behaviour and semen quality  of bulls, with temperature, humidity and seasonal  variations being significant contributors. Stressors  related to sexual behaviour, such as the  transportation of animals for mating or  confrontations between bulls, can have detrimental  effects on semen quality. Furthermore, adequate  peri-conception and post-natal nutrition received by  the calf also affects its postnatal health, gonadal  development, gamete quality and the hormonal  status ultimately affecting its sexual expression and  behaviour. Lastly, bulls that sustain physical injuries  or infections from sexual encounters may exhibit a  decline in sexual behaviour, impacting their semen  quality. This paper presents a literature review on  sexual behaviour of bulls and its consequences for  welfare and quality semen production with special  focus on in Indian native cattle and buffaloes.
Keywords: behaviour; bull; environment; libido; quality; semen